1995
DOI: 10.3109/10611869509015934
|View full text |Cite
|
Sign up to set email alerts
|

A Commentary on Morphological and Quantitative Aspects of Microparticle Translocation Across the Gastrointestinal Mucosa

Abstract: It is now generally accepted that particulates in the nano-range (< 1 micron) can and do cross the intestinal mucosa. However, the issue is less well resolved for particles in the micro-range (> 1 micron) and this is discussed in relation to the variety of experimental designs present in the literature. Emphasis is placed on the relative contributions of quantitative bulk tissue analysis with respect to qualitative and quantitative morphological analysis. The discussion is extended to observations on factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The study suggests that the metallo-NPs were taken up by a Trojan-horse type mechanism and that the cell membrane of lung epithelia cells seems to have improved barrier capacities for metal ions compared to metal particles. The pathway and extent of uptake of insoluble particles through the digestive tract are known to be size-dependent (Hodges et al, 1995;Donaldson et al, 1998). Chen et al (2006) compared small size copper nanoparticles (23.5 nm) and copper microparticles (17 μm) administered by oral gavage to mice and found that nanoparticles induced substantial toxicological effects and heavy injuries to kidney, liver and spleen of experimental mice which was not the case for copper microparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The study suggests that the metallo-NPs were taken up by a Trojan-horse type mechanism and that the cell membrane of lung epithelia cells seems to have improved barrier capacities for metal ions compared to metal particles. The pathway and extent of uptake of insoluble particles through the digestive tract are known to be size-dependent (Hodges et al, 1995;Donaldson et al, 1998). Chen et al (2006) compared small size copper nanoparticles (23.5 nm) and copper microparticles (17 μm) administered by oral gavage to mice and found that nanoparticles induced substantial toxicological effects and heavy injuries to kidney, liver and spleen of experimental mice which was not the case for copper microparticles.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the food and digested food components can interact with the microencapsulated formulation and provide an additional barrier against early release of the encapsulated bioactives. Therefore in any gut transit and absorption study, the amount of gavaged material and the formulation of the introduced matrix and particle size are important from the point of accelerated gastric emptying together with the level of fasting (Chaudhuri & Fink, 1990;Hodges, Carr, Hazzard, O'Reilly, & Carr, 1995;Lentle & Jannsen, 2008;Lentle & Jannsen, 2010;Patten et al, 2009). …”
Section: Bioactive Distribution In the Lumenmentioning
confidence: 99%
“…For the triacylglycerols, microencapsulation would be expected to retain the lipids within the emulsion droplet in the original prepared emulsion. If the interface of the oil droplet is readily displaced by bile salts once in the GI tract and allows attachment of gastric and pancreatic lipases, then the larger surface area of the lipid droplets may make them more readily digested than the lipids in the control suspensions if the latter has a larger particle size (Armand et al, 1992;Hodges et al, 1995). However, if the interface of the original emulsion resists displacement by the bile salts, then this would contribute to retarded lipolysis.…”
Section: Bioactives In Liver and Bloodmentioning
confidence: 99%
“…It is generally accepted that the uptake of insoluble, particulate matter through the digestive tract occurs in low quantities, and that the pathway and amount of particle uptake is size dependent 1,2. Research on the passage of microparticles through the gut lumen into the body has shown that particles in the micrometer size range enter the body by a process called persorption: the paracellular uptake of microparticles from the digestive tract into the body 3.…”
Section: Introductionmentioning
confidence: 99%